Analisis Kemampuan Literasi Sains Peserta Didik dengan Pendekatan TaRL Pembelajaran IPAS - Mardiyah, Naili; Nuvitalia, Duwi; Purnamasari, Veryliana; Warsiti, Bernadeta (Education Journal : Journal Educational Research and Development, 2024)
This study aims to determine the science literacy ability of students using the Teaching at the Right Level (TaRL) approach. The method used in this study is qualitative descriptive. The research was carried out by describing descriptively the science literacy skills of 5th grade elementary school students of SD Bukit Aksara, Semarang City. The research was carried out in the even semester of the 2023/2024 Academic Year in conjunction with PPL 1 PPG Pre-service which was held from March to May 2024. The research was conducted on all 5A students at SD Bukit Aksara, Semarang City, totaling 21 students. The instrument used a science process skills questionnaire. The use of the Teaching at Right Level (TaRL) approach in social science learning is effective in improving students' literacy skills. This can be seen from the results of the questionnaire which shows that most students have a positive attitude towards science, a good assessment of scientific approaches, and a high awareness of the environment. From the science literacy ability questionnaire data, students in class 5A of SD Bukit Aksara have a level of science literacy ability with an overall average of 75% with a good category